Effect of long-term testosterone replacement therapy on arterial stiffness and systemic endothelial function in male patients with hypogonadism. (14th October 2021) - Ioakeimidis, N; Angelis, A; Rokkas, K; Terentes-Printzios, D; Saad, F; Tousoulis, D; Tsioufis, K; Vlachopoulos, C
Abstract: Purpose: The study aims at providing the long-term effect of testosterone replacement therapy on systemic endothelial function, aortic stiffness and wave reflections in men with testosterone deficiency (TD). Methods: This is a randomized single-center double-blind placebo-controlled trial involving 24 men (aged 51±9 years) with erectile dysfunction (ED) and total testosterone (TT) levels below 3.5 ng/ml randomised to receive either intramuscular (i.m) testosterone undecanoate (TU) injections (1000 mg as a single 4 mL i.m. injection at 0, 6, 18, 30 and 42 weeks) or an identical placebo at similar time points. A TU /placebo 2:1 randomization list was generated and patients were centrally assigned to one of the two arms, consecutively. Central blood pressure (BP), augmentation index (AIx), carotid-femoral pulse wave velocity (PWV) and brachial flow mediated dilatation (FMD) were measured at baseline, and at 18, 24, 30 and 44 weeks. Results: The changes in central systolic BP and pulse pressure were more potent in the TU group compared to placebo group, however the decreases in these parameters were not statistically significant in point-of-time and time and group interaction. Repeated measures ANOVA revealed that the in point-of-time decrease in AIx was statistically significant in the group receiving TU (P=0.029) compared to men receiving placebo (figure). The maximal response in AIx was observed at 18 and 24 weeks (by 4.2% and 5.0%, respectively, all P<0.05). The interaction of time and group was also statistically significant (P=0.012) indicating significant differences between the treatment groups and time. PWV in the TU therapy group decreases during the whole study period, however the in point-of-time change was not statistically significant (P>0.05, figure). In men receiving TU the change in PWV was marginally significant only at 24 weeks (reduction by 0.34 m/s, P=0.05), whereas there were no significant differences in PWV between baseline and all other assessment time points. TU minimally increased brachial FMD up to 24 weeks (increase by 0.15%, P=0.05) from the beginning of therapy and the in point of the time change was not statistically significant (P>0.05, figure). Conclusion: The 44-week TU i.m therapy was associated with a beneficial sustained effect on central AIx wave reflections thorough the whole study period. PWV decreased, particularly at 24 weeks, however the change in aortic elastic properties during the whole study session was not significant. Systemic endothelial function minimally improved compared to placebo. Given that AIx is an independent marker of cardiovascular disease and predictor of the corresponding risk, these findings have important implications to assess the effect of testosterone replacement interventions on cardiovascular performance and the corresponding risk of patients with ED and TD. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Bayer Pharmaceuticals